Accesul la informaţiile de interes public – obligaţie legală în sarcina autorităţilor administraţiei publice. Studiu de caz privind gradul de accesibilitate al informațiilor de interes public comunicate din oficiu - Ana Elena RANTA (Revista Transilvană de Ştiinţe Administrative, 2014)
Acces to information of public interest has be-come, in the recent years, one of the most important criterion, according to which a society is assessed as a functional democracy, and, at the same time, is one of the fundamental principles of citizens – public authorities relations. In this feld, changes made to the legal framework of post-communist countries have occurred progresively and slowly, after more than ten years since the fall of the communist re-gimes. The adoption of the law on access to infor-mation of public interest has opened the path to a transparent process of governing and has led to the increase of public institutions’ responsibilities but the mere existence of this law is not a guarantee for signifcant changes unless completed by sustained efforts coming mainly form public administration.